Selection of reference genes for normalization of microRNA expression in sugarcane stalks during its interaction with Colletotrichum falcatum - Nandakumar, M. (3 Biotech, 2021)
The microRNAs role in various cellular and metabolic functions is gaining more limelight in line with second-generation NGS technology. For the validation of candidate miRNA genes, the quantitative real-time PCR is the widely trusted and efficient method to follow. Sugarcane miRNAs are less explored in sugarcane defense response during their interaction with Colletotrichum falcatum inciting red rot. Further, for RT-qPCR experiments involving sugarcane miRNA expression studies, a stable internal reference gene is required. Hence, we have taken a study involving 20 candidate genes to identify stable expressing reference genes using NormFinder, geNorm, BestKeeper, and deltaCt statistical algorithms. The candidate reference genes included miRNAs and protein-coding genes. The results indicated that there is a variation in ranking among the algorithms. We found miR1862c as the stably expressed miRNA reference gene among the candidates and miR444b.2 along miR1862c formed the best reference gene pair combination, which can be used in the experiments aiming to explore sugarcane miRNAs in the defense mechanism against C. falcatum. The stable miRNA reference gene was further validated with other lesser stable reference gene candidates to assess the effect of stable reference genes during normalization. The present study evaluating the sugarcane miRNAs as reference genes for normalizing RT-qPCR expression data involving miRNAs during sugarcane × C. falcatum interaction is the first of its kind. Further, this systematic approach can be followed to assess the reference gene in various experimental conditions involving sugarcane miRNAs.